Estudo sobre o roleteamento do aço ABNT 4140 temperado e revenido - Carlos Artur Alevato Leal (2020)
The deep rolling is an operation that consists of the plastic deformation of a surface through the passage of balls, rollers or rounded tips under constant pressure against the material. This operation, considered a mechanical surface treatment, emerged as an alternative to shot peening and seeks, mainly, the induction of compressive residual stress on the surface with improvement in the surface quality. Since the last decades, this treatment has been applied to several areas of industry, but further research is required on the influence of this operation on the fatigue life and microstructure alterations of various materials. In this work, the influence of the deep rolling parameters pressure, speed (tangent to the surface) and feed on the surface integrity, mechanical fatigue life by rotating flexion, rolling temperature, microstructure and microhardness of quenched and tempered AISI 4140 steel (39 HRC) is investigated. The results indicated that deep rolling pressure (Pr) is statistically significant on the arithmetic mean deviation (Ra), maximum peak height (Rp), maximum valley depth (Rv) and mechanical fatigue life. Deep rolling speed (Vr) is statistically significant on Ra and Rv and deep rolling feed (fr) on Ra and Rv. Deep rolling increases the fatigue life under almost all conditions tested, reaching in some condition improvements of more than 400% when compared to the non-rolled workpiece. The temperature during the deep rolling did not reach values considered relevant for changing the workpiece microstructure. The microstructure presents a region with plastic flow below the rolled surface, with the highest pressure (300 bar) producing a thin white layer on the surface. The electron back scattered diffraction indicated the presence of a ferritic matrix and grain size approximately of 3 μm. The highest deep rolling pressure increased microhardness up to 45 μm in depth.